MINIMALS SECURITY HOUSE IN YOGYAKARTA - Sugestiyadi, Bambang (Jurnal Penelitian Saintek, 2007)
Yogyakarta could be the mirror of "Nusantara" since it had been accumulated with people from "all around the Nusantara for study. Yogyakarta could be considered a town which would grow as "Semi Metropolis" city. there for physical facilities are needed. This research was conducted to know the minimalism architecture development in house development in Yogyakarta.The research was carried out on qualitative design. Data collectedwith observation, visualization, skates maker, photo documentation and deeply and structurally. interview Relevant documentation from some conected departments was taken. Data analyzed with inductive method. It means that all data not to reveal hypothesis but focus on abstract formation based on parts which were collected, than grouped. Triangulation was conducted for testing data validity.The results showed that: (a) House and housing development until2004 decade still dominated by Mediteran Style, Tropical House Style, Classical House Style with ornamens, (b) The Minimalism House Style in architecture focuses on essential and functional things. The Minimalism Style dominated by elementary geometrical form without ornamen or decoration, and it became its character. It began to grow since 2004 to 2006, in Sleman Regency, Yogyakarta.